The Relationship Between Cha2ds2-Vasc Scores And The Degree of TIMI Flow in Patients With Acute St-Segment Elevation Myocardial Infarction Who Underwent Primary Percutaneous Coronary Intervention at Dr. Saiful Anwar Malang - Aji, Bayu; Widito, Sasmojo; Anjarwani, Setyasih; Kurnianingsih, Novi; Ruspiono, Evit (Heart Science Journal, 2024)
Background: Suboptimal reperfusion of the compromised myocardium in the area of the culprit coronary arteries is one of the main problems associated with primary PCI that need reliable risk stratification methods to accurately predict the occurrence of decreased TIMI flow given its complex pathophysiology. Some parameters are included CHA2DS2-VASc score.Objective: To understand the relationship between CHA2DS2-VASc and the decreased TIMI flow in STE-ACS patients who had underwent primary PCI at RSUD dr. Saiful Anwar Malang.Material and Methods: The study was cohort retrospective with the inclusion criteria being all STE-ACS patients who underwent primary PCI in RSUD Dr. Saiful Anwar Malang from January 2018 – August 2023. Patients were assigned to TIMI flow grade <3 group (N =169) and TIMI flow grade 3 (N = 677) according to TIMI Flow degree after primary PCI. All the patient’s angiogram were evaluated for TIMI score and CHA2DS2-VASc score is based on a guideline. We concluded data in SPSS program and used the Spearman test and p value of .05 was considered as significant.Result: From a total sample of 846 patients, the correlation between STE-ACS onset and TIMI flow indicates that a higher number of patients with STE-ACS onset <12 hours was found in the TIMI flow <3 and 3 groups (p=0.000). The cutoff CHA2DS2 VASC score's sensitivity and specificity values were ascertained using ROC analysis with cut off value 2.5. The incidence of decreased TIMI flow rate was more significant in the CHA2DS2-VASc ≥3 group with DM (+) and age ≥64 (OR value 0.156, p=0.000) than in the CHA2DS2-VASc ≥3 group without DM and age < 64. With an OR value of 2.94 (p=0.000), Killip class > 2 is another powerful predictor of lower TIMI flow.Conclusion: The only variables in the CHA2DS2-VASc score component that are most strongly associated with the risk of reducing the degree of TIMI flow are DM, age, and Killip class.